2017
DOI: 10.18632/oncotarget.19901
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of citrin deficiency in an infant with intrahepatic cholestasis: identification of a 21.7kb gross deletion that completely silences the transcriptional and translational expression of the affected SLC25A13 allele

Abstract: Neonatal Intrahepatic Cholestasis caused by Citrin Deficiency (NICCD) arises from biallelic SLC25A13 mutations, and SLC25A13 analysis provides reliable evidences for NICCD definite diagnosis. However, novel large insertions/deletions in this gene could not be detected just by conventional DNA analysis. This study aimed to explore definite diagnostic evidences for an infant highly-suspected to have NICCD. Prevalent mutation screening and Sanger sequencing of SLC25A13 gene just revealed a paternally-inherited mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Neonatal Intrahepatic Cholestasis caused by Citrin Deficiency (NICCD) in neonates or infants (Ohura et al, 2001; Tazawa et al, 2001; Tomomasa et al, 2001), adult-onset citrullinemia type II (CTLN2) in adolescents or adults (Kobayashi et al, 1999), and Failure to Thrive and Dyslipidemia caused by Citrin Deficiency (FTTDCD) at pediatric age beyond 1 year (Song et al, 2011; Saheki and Song., 2017). To the best of our knowledge, although the clinical and molecular characteristics of NICCD has been studied for years (Ohura et al, 2007; Chen et al, 2013; Song et al, 2013; Ricciuto and Buhas, 2014; Zeng et al, 2014; Wang et al, 2015; Lin et al, 2016; Zhang et al, 2017), patients with NTCP deficiency complicated by NICCD have never been reported thus far.…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal Intrahepatic Cholestasis caused by Citrin Deficiency (NICCD) in neonates or infants (Ohura et al, 2001; Tazawa et al, 2001; Tomomasa et al, 2001), adult-onset citrullinemia type II (CTLN2) in adolescents or adults (Kobayashi et al, 1999), and Failure to Thrive and Dyslipidemia caused by Citrin Deficiency (FTTDCD) at pediatric age beyond 1 year (Song et al, 2011; Saheki and Song., 2017). To the best of our knowledge, although the clinical and molecular characteristics of NICCD has been studied for years (Ohura et al, 2007; Chen et al, 2013; Song et al, 2013; Ricciuto and Buhas, 2014; Zeng et al, 2014; Wang et al, 2015; Lin et al, 2016; Zhang et al, 2017), patients with NTCP deficiency complicated by NICCD have never been reported thus far.…”
Section: Introductionmentioning
confidence: 99%
“…According to the ACMG guidelines, the pathogenicity analysis is PVS1 + PM2 + PP4, so it is likely pathogenic. Exon deletion is a rare variant type among SLC25A13 variants, which are mainly caused by large fragment deletion, including exon deletion, such as c.329–154_468 + 2352del2646bp (deletion of exon 5) ( 12 ), c.70–862_c.212 + 3527 del4532bp (deletion of exon 3) ( 13 ), Ex16 + 74_IVS17-32del516 (deletion of exon 17) ( 14 ), c.329–1687 -c.468 + 3865del5692bp (deletion of exon 5) ( 15 ), c.1019_1177 + 893del (deletion of exon 11) ( 16 ), c.1312–2860_1452 + 988del (deletion of exon 14) ( 17 ), c.1312–4144_1452 + 3373del (deletion of exon 14) ( 17 ) and c.3251 _c.15 + 18443del21709bp (deletion of exon 1) ( 18 ). Partial abnormal splicing of partially intron regions leads to exome deletions in mRNA, such as IVS4ins6 kb (skipping of exon 5) ( 19 ), IVS11+1 G > A (skipping of exon 11) ( 20 ), IVS15 + 1G > T (skipping of exon 15) ( 21 ) and IVS13+1G > A (skipping of exon 13) ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Presymptomatic testing is offered to individuals with a known genetic disorder in the family, whereas postsymptomatic genetic testing should be offered to individuals suspected clinically to be affected by genetic disease, ranging from gene specific to panel specific to WGS/WES. 37 Some of the disorders which can be unveiled with genomic testing are neonatal intrahepatic cholestasis caused by citrin deficiency (mutations in SLC25A13), 38 progressive familial intrahepatic cholestasis 39 (mutations in either ATP8B1 or ABCB11), Alagille syndrome (mutations in either JAG1 or NOTCH2), Alagille syndrome and Dubin-Johnson syndrome (mutations in ABCC2). In a recent study by Togawa et al, they analyzed 109 Japanese infants with cholestasis and made a molecular genetic diagnosis in 26% of their cohort (28/109).…”
Section: Role Of Genomics In the Evaluation Of Nc: Genetic Cholestasismentioning
confidence: 99%